Mesophilic and Thermophilic Biomethane Production by Co-Digesting Pretreated Petrochemical Wastewater With Beef and Dairy Cattle Manure - Siddique, Md. Nurul Islam; Mimi Sakinah, A. M.; Zularisam, A. W. (Elsevier, 2014)
The use of pretreated petrochemical wastewater as provender wastewater for anaerobic degradation was explored in a continuous stirred tank reactor with dairy and beef cattle manure, under both mesophilic and thermophilic states. The co-digestion of the wastewaters contributed 50% enhancement in methane production, followed by a 98 ± 0.5% reduction in chemical oxygen demand at 10 days hydraulic retention time. No VFA aggregation was identified. In comparison with the digestion of PWW alone, methane yield increased by 50–60% under mesophilic conditions and 50–65% under thermophilic conditions due to co-digestion.